THE IMPACT OF HOTEL TAX, RESTAURANT TAX AND ENTERTAINMENT TAX ON THE REGIONAL ORIGINAL INCOME OF SERANG REGENCY FOR THE 2018-2024 PERIOD - Puput Putri Handayani; Dini Martinda Lestari; Evi Dora Sembiring; Ade Samsinar; Amyati Amyati; Sari Putri Pertiwi (International Journal of Multidisciplinary Research and Literature, 2026)
Local Own-Source Revenue (PAD) is one of the main indicators used to assess a region’s fiscal independence, consisting of local taxes, retributions, income from separated regional assets, and other legitimate revenues. Serang Regency has considerable potential to increase PAD, particularly from the hotel, restaurant, and entertainment tax sectors. However, the realization from these three sectors has not yet been optimal. This study aims to analyze the influence of hotel tax, restaurant tax, and entertainment tax on the PAD of Serang Regency during the 2018–2024 period, both partially and simultaneously. The research uses a quantitative approach with multiple linear regression analysis based on secondary data from the Regional Revenue Agency (Bapenda). The results show that partially, the restaurant tax has a significant effect on PAD, while the hotel and entertainment taxes do not have a significant effect. However, simultaneously, all three types of taxes significantly affect PAD. Therefore, the restaurant tax is considered the most promising sector for development, while the management strategies for hotel and entertainment taxes should be evaluated to enhance their contribution to Serang Regency’s PAD.